N2O selectivity in industrial NH3 oxidation on Pt gauze is determined by interaction of local flow and surface chemistry: A simulation study using mechanistic kinetics - Haas, M.; Nien, T.; Fadic, A.; Mmbaga, J. P.; Klingenberger, M.; Born, D.; Etzold, Bastian J.M.; Hayes, R. E.; Votsmeier, M. (Chemical Engineering Science, 2022)
Despite significant effort spent on the investigation of catalytic oxidation of ammonia on platinum at the molecular scale, there is surprisingly little work that investigates the behavior of the established reaction mechanisms under industrial conditions in the presence of mass transfer limitations. This paper presents reactive flow simulations of ammonia oxidation on platinum gauzes under industrial operating conditions, combining a mechanistic description of the surface chemistry with the computation of the flow-, temperature- and concentration fields around the platinum wires. Overall, the simulations yield temperature- and concentration fields, as well as integral N2O selectivity in line with industrial experience and (limited available) experimental data. In particular, the simulations predict the experimentally observed decrease of the integral N2O selectivity with increasing wire diameter, increasing wire-to-wire distance, decrasing flow velocity, and increased surface area due to surface reconstruction. The main result of the paper is that the local interaction of the flow field with surface chemistry leads to a variation in the local N2O (and N2) selectivity across the gauze: • The N2O and N2 selectivity is higher on the front side of a wire than on the rear side. • A reduced N2O selectivity is observed where one wire is shadowed by another wire. • Increased N2O selectivity is observed at stagnation points where upstream wires direct the flow so that it hits a downstream wire with higher velocity.These examples show that - through the flow directing effect of the upstream wires - the selectivity on an individual wire is influenced by the presence of other wires. This observation provides a mechanistic explanation for the industrial observation that optimized gauze geometries can lead to reduced N2O formation. Understanding the effect of local mass transfer on the selectivity provides a guideline for a further rational optimization of gauze geometries for improved N2O and N2 selectivity. To analyze the robustness of the simulation results towards uncertainties in the reaction mechanism, a sensitivity analysis is performed, and the selectivity order defined as nSN2O,NH3=∂lnSN2O/∂lncNH3 (i.e. the response of the N2O selectivity SN2O to changes in the near-wall NH3 concentration cNH3) is identified as the decisive property of a reaction mechanism, that controls the response of the local selectivity to variations in the flow field. This suggests that future mechanistic work should focus on a more precise determination of this selectivity order nSN2O,NH3.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Ammonia; Flow simulation; Mechanistic kinetics; N; Ostwald process; Platinum gauze